The Concept of Modeling the Risk of Green Building Implementation and their Impact on the Application of the Pentuple Bottom Line: Literature Review - Susanto, Sony; Ciptadi, Gatot; Hanani, Nuhfil; Anwar, M. Ruslin; Marjono, Marjono (Jurnal Pembangunan dan Alam Lestari, 2023)
Construction is the most significant contributor to global energy consumption. Several studies are currently being conducted to assess the risk of green construction projects, and risk modeling that considers sustainable variables is required. This study aims to evaluate, assess, and analyze the current literature on the concept of modeling the risk of green on the application of the pentuple bottom line, as well as to identify the associated themes and gaps. The Scopus databases were searched for risk green buildings using keywords such as "Risk," "green," and "building." Several papers were discovered and filtered based on their title, abstract, and keyword relevance. More articles were cross-referenced and filtered based on title, abstract, and keyword relevance—the method with Prisma protocol and Vosviewer. From 2006 to 2022, 1333 publications were discovered and analyzed using 12 bibliometrics. The approach to the likelihood and impact of the evaluation model is defined by taking five sustainable components into account (economic, social, environmental, religious, and technological). RGB = (Rp + Rse + Rm + Rt + Rs /5) is the outcome of the green building risk assessment formula. Keywords: green building, impact, risk, modeling, pentuple